The 1909 river Douro flood: a contribution to its study from the historical archives of the portuguese environmental agency - Batista Vieira, António Avelino; da Silva Costa, Francisco (Investigaciones Geográficas, 2017)
Between 17 and 25 December 1909, the population of the city of Porto and Gaia watched helplessly the destruction of their riverside areas, by the flood of the Douro River. The flood caused immense losses on both banks of the Douro, forcing the intervention of various state agencies for their subsequent rehabilitation. From a set of documents of the authorship of the 1ª Direção dos Serviços Fluviais e Marítimos was possible to identify the interventions that were planned, as well as the progress of work, and, from there, also identify the areas affected by this catastrophic event and the real extent of their effects on riverside areas of Porto and Gaia.